2023
DOI: 10.3390/agriculture13030601
|View full text |Cite
|
Sign up to set email alerts
|

Zoning of Potential Areas for the Production of Oleaginous Species in Colombia under Agroforestry Systems

Abstract: Due to the need to develop more agroforestry systems, the Moringa oleifera, Olea Europea, Glycine max, Brassica napus, Helianthus annuus, and Jatropha curcas are identified as unconventional species for their expansion under these systems in Colombia. With the Colombian Environmental Information System (SIAC) database, zoning was carried out according to the agroclimatic species requirements and optimal coverage for their production. As a result, a total area of 212,977.2 km2 was identified, mainly including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The analysis focused on soil degradation from boot palm oil (PO) and JCL cultivation, as discussed by [34] and [33]. Additionally, the suitability of JB production in the non-interconnected areas was examined based on the agroclimatic compatibility of oleaginous species for different regions in Colombia as developed by [35]. Finally, to verify the benefits of JB as a fuel, the outcomes of the present work were compared with those obtained in previous research.…”
Section: Economic and Environmental Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis focused on soil degradation from boot palm oil (PO) and JCL cultivation, as discussed by [34] and [33]. Additionally, the suitability of JB production in the non-interconnected areas was examined based on the agroclimatic compatibility of oleaginous species for different regions in Colombia as developed by [35]. Finally, to verify the benefits of JB as a fuel, the outcomes of the present work were compared with those obtained in previous research.…”
Section: Economic and Environmental Assessmentmentioning
confidence: 99%
“…Lozano-Castellanos et al [35] studied the potential of oleaginous species in Colombia, and they found that, in Colombia, 18.65% (212,977.2 km 2 ) of the territory has the agroclimatic compatibility needed to produce oilseeds such as JCL. This land is distributed mainly in 10 of the 32 departments of Colombia, some of which include many non-interconnected areas with excellent potential to use JCL for biodiesel production and thus attain selfsufficiency.…”
Section: Economic and Environment Assessmentmentioning
confidence: 99%